Psychometric study of the Russian version of the Obsessive-Compulsive Drinking Scale - S. G. Klimanova; M. A. Bornovalova; P. Emmanuel; A. Zaarur; A. A. Berezina; A. V. Trusova; K. V. Rybakova; E. M. Krupitsky (Обозрение психиатрии и медицинской психологии имени В.М. Бехтерева)
Craving is one of the central symptoms of alcohol use disorder. Currently, there is no single accepted definition, model, or standardized approach to assessing craving for alcohol use, but the phenomenon is extensively studied in the field of addiction research. The Obsessive-Compulsive Drinking Scale was developed based on the hypothesis that both obsessive-compulsive disorder and alcohol use disorder have similar symptoms. The purpose of this study was to examine the factor structure as well as the convergent, discriminant, and criterion validity of the Obsessive-Compulsive Drinking Scale. 222 patients with Alcohol Use Disorder undergoing inpatient treatment (163 men (73,42%), average age 42,67±10,06 years old, average age of the onset of alcohol use disorder 32,19±8,57 years old) were recruited for the study. The following methods were used: clinical interview, Obsessive-Compulsive Drinking Scale, Penn Alcohol Craving Scale, Motivation for Alcohol Consumption, and Barratt Impulsiveness Scale. The results of the study confirmed two-factor structure of the scale; however, the goodness-of-fit indices slightly differed from acceptable cut-off values. The scale had acceptable internal consistency and convergent validity. Discriminant validity was moderate. The analysis of criterion validity revealed a negative correlation between the factor “Compulsions” and age of the first alcohol drink, start of the regular alcohol use, and age of the first inpatient treatment for alcohol use disorder. Participants with daily use had significantly higher scores on both factors compared to the participants with heavy drinking episodes.